Enhancing the Quality of Living Environment - the Utilization of Carbon Dioxide as a Green Industry Innovation - Mufidah, Ida Umarul (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2023)
The rapid growth in the productivity of the world's chemical industry has had adverse environmental impacts. One of the efforts to protect the environment is by reprocessing carbon dioxide. This research is an initiative to link the use of CO2 with the formation of green industrial innovation in the long term. A qualitative-descriptive approach is implemented to achieve this goal, aided by a literature review. The research results show that CO2 is not only produced from non-fossil energy residues but also from other fossil energy sources. The importance of campaigning for developing a carbon capture and storage technology that is actively supported by all parties is the key to the success of tackling the future climate change problem. Keywords: utilization; carbon dioxide (CO 2 ); green industry; sustainable development Abstrak Pesatnya pertumbuhan produktivitas industri kimia dunia telah menimbulkan dampak lingkungan yang merugikan. Salah satu upaya menjaga keberlanjutan lingkungan adalah melalui pengolahan kembali karbondioksida. Penelitian ini diharapkan dapat menjadi salah satu cara untuk menghubungkan penggunaan CO2 sebagai inovasi industri hijau untuk jangka panjang. Dalam mencapai tujuan ini, diterapkan pendekatan deskriptif kualitatif yang didukung oleh kajian kepustakaan. Hasil penelitian menunjukkan bahwa CO2 tidak hanya diproduksi dari sisa energi non-fosil tetapi juga dari sumber energi fosil lainnya. Pentingnya kampanye terkait teknologi penangkapan dan penyimpanan karbon yang didukung peran aktif dari semua pihak menjadi kunci keberhasilan dalam penanganan masalah perubahan iklim di masa depan. Kata kunci: pemanfaatan; karbondioksida (Co 2 ); industri hijau; pembangunan berkelanjutan